2020
DOI: 10.3390/ani10101908
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Feeding Unweaned Dairy Beef Cattle to Improve Their Health

Abstract: In order to answer the question of whether nutritional interventions may help to reduce the incidence of respiratory disease in dairy beef calves at arrival, the present review is divided in three sections. In the first section, the nutrition of calves previous to the arrival from the origin farm to the final rearing farm is reviewed. In the second section, the possible consequences of this previous nutrition on gut health and immune status upon arrival to the rearing farm are described. The main consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…Glucose is an upstream regulator of 26 genes associated with BRD, and if glucose homeostasis is disrupted, hypoglycemia or hyperglycemia occurs 55 . Decreases in glucose as observed in the present M. haemolytica challenge were previously reported in BRD studies as a result from natural or arti cially induced infections, LPS injections, stress-related to transport, and receiving calves 34,55,56 . It has been suggested that, in addition to the metabolic changes caused by the immunological response, the decrease in glucose levels is also due to the hypoglycemic effect of BRD and the decline in diet due to the discomfort caused by the respiratory signs 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose is an upstream regulator of 26 genes associated with BRD, and if glucose homeostasis is disrupted, hypoglycemia or hyperglycemia occurs 55 . Decreases in glucose as observed in the present M. haemolytica challenge were previously reported in BRD studies as a result from natural or arti cially induced infections, LPS injections, stress-related to transport, and receiving calves 34,55,56 . It has been suggested that, in addition to the metabolic changes caused by the immunological response, the decrease in glucose levels is also due to the hypoglycemic effect of BRD and the decline in diet due to the discomfort caused by the respiratory signs 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Because this is a slow process, supplying the energy demands during the cell signaling cascades and immune response caused by PAMPs recognition requires metabolism reprogramming by immune cells, where alternative energy sources such as triglycerides and proteins are used for ATP production [52][53][54] . Glucose is an upstream regulator of 26 genes associated with BRD, and if glucose homeostasis is disrupted, hypoglycemia or hyperglycemia occurs 55 . Decreases in glucose as observed in the present M. haemolytica challenge were previously reported in BRD studies as a result from natural or arti cially induced infections, LPS injections, stress-related to transport, and receiving calves 34,55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Ireland is an example of a country with an intensive pasturebased system of milk production with a seasonal calving pattern as described above. About 40% of all calves born in Irish dairy herds are reared for beef primarily in pasture-based systems of production, while almost 12% of dairy calves 180 k dairy calves [predominately male-out of approximately 1.6 m dairy cows; (9)] are shipped unweaned to the European continent for veal [or beef- (10)] production. Export of calves to a second country is a contentious practice with opponents arguing not to transport young unweaned animals over long distances because it poses major threats to their welfare (11).…”
Section: Introductionmentioning
confidence: 99%
“…The age at which the calves are transported (c. 3 weeks old) coincides with the decrease in maternal antibody and the immaturity of the humoral immune system (15) leaving them more susceptible to environmental infections. There are also concerns with calves' fate at the destination, particularly with veal, but also with intensive beef production, relating to feeding and housing practices and associated antimicrobial use (3,10,16). There is considerable room for improvement to calf transport and veal production systems and such changes might make these options for surplus calves more sustainable and ethically acceptable from a societal point of view (3).…”
Section: Introductionmentioning
confidence: 99%
“…The veal industry is an important market for male calves born on dairy farms (Bokma et al, 2020). These male calves together with some surplus female calves might be considered by-products for the dairy sector because they have a low financial value and they may not represent a priority (Devant and Marti, 2020). As a consequence, these animals might receive poor post-natal care, including feeding low amounts of colostrum of moderate quality and poor navel disinfection after birth (Mee et al, 2008;Renaud et al, 2017).…”
Section: The Veal Sector and The Use Of Antimicrobialsmentioning
confidence: 99%